Polyunsaturated fatty acids and amino acids for athletes: impact on physical activity - Nenenko N.D.; Stogov M.V.; Tolokova M.P.; Kamalova M.F. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to еxamination of the effectiveness of polyunsaturated fatty acids (PUFA) and branched side chain amino acids (BCAA) in physical education. Methods and structure of the study. The process of locating relevant literary information involved utilizing the publicly accessible electronic repositories of scholarly publications, PubMed and eLibrary. Results and conclusions. The findings suggest that the use of dietary supplements containing polyunsaturated fatty acids (PUFA) and branched-chain amino acids (BCAA) in the context of physical training can effectively enhance muscle performance and resilience. The literature suggests that the optimal duration of PUFA supplementation is eight weeks, with a daily dose of 4-5 grams. For BCAA, the recommended duration is no more than 16 weeks, with a daily dose of 2-10 grams. When these supplements are combined, they can work together to accelerate muscle recovery after exercise.